Synchronization and Delay Techniques for Driving lMHz Totem-Poled Power MOSFET Configuration - Zakaria, Nurazlin (Universiti Teknologi Petronas, 2010)
This project discusses about the synchronization and delay techniques that are suitable for totem-poled power MOSFET configuration operating at high speed. Modification has been made to the proposed synchronization circuit fur earlier PWM controllers that have an operating frequency ranging from 80 kHz to 120 kHz. Experimentation is carried out to obtain the most suitable means in synchronizing the PWM signals and adding delay function. The synchronization and delay network is able to operate at high switching frequency of 1 MHz. In addition, two different sets of complementary square-wave are achieved at duty cycle of 50 % and 20 %. The result with 20 % duty cycle can be used for previous work in investigation of high frequency effects on soft switch-switched synchronous rectifier buck converter